Southern Annular Mode-like changes in southwestern Patagonia at centennial timescales over the last three millennia - Moreno, Patricio (2014)
Late twentieth-century instrumental records reveal a persistent southward shift of the Southern Westerly Winds during austral summer and autumn associated with a positive trend of the Southern Annular Mode (SAM) and contemporaneous with glacial recession, steady increases in atmospheric temperatures and CO2 concentrations at a global scale. However, despite the clear importance of the SAM in the modern/future climate, very little is known regarding its behaviour during pre-Industrial times. Here we present a stratigraphic record from Lago Cipreses (51S), southwestern Patagonia, that reveals recurrent B200-year long dry/warm phases over the last three millennia, which we interpret as positive SAM-like states. These correspond in timing with the Industrial revolution, the Mediaeval Climate Anomaly, the Roman and Late Bronze Age Warm Periods and alternate with cold/wet multicentennial phases in European palaeoclimate records. We conclude that SAM-like changes at centennial timescales in southwestern Patagonia represent in-phase interhemispheric coupling of palaeoclimate over the last 3,000 years through atmospheric teleconnections.